2020
DOI: 10.1007/s12571-020-01056-5
|View full text |Cite
|
Sign up to set email alerts
|

Can household dietary diversity inform about nutrient adequacy? Lessons from a food systems analysis in Ethiopia

Abstract: This study examined the use of the household dietary diversity score (HDDS) to assess household nutrient adequacy in Ethiopia. It also examined the correlates of HDDS following the food systems framework. Results show that the average nutrient consumption in Ethiopia varies by place of residence and by income profile, where households in urban areas and those in the higher income quintiles rank favorably. Among 13 nutrients under study, we found nutrient inadequacy for fat, calcium, zinc, riboflavin, niacin, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
3
21
2
Order By: Relevance
“…We found that on average households in Addis Ababa, Ethiopia, consumed 8.5 out of 12 food groups in the past 7 days. This is quite similar to the 7.9 found for urban areas by Mekonnen et al (2020), who base their results on a nationally representative survey for Ethiopia for 2015/ 16. That our number is somewhat higher could be due to the rapid economic development of the country in recent years and because Addis Ababa is a relatively wealthy city within the country.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We found that on average households in Addis Ababa, Ethiopia, consumed 8.5 out of 12 food groups in the past 7 days. This is quite similar to the 7.9 found for urban areas by Mekonnen et al (2020), who base their results on a nationally representative survey for Ethiopia for 2015/ 16. That our number is somewhat higher could be due to the rapid economic development of the country in recent years and because Addis Ababa is a relatively wealthy city within the country.…”
Section: Discussionsupporting
confidence: 86%
“…A high-quality diet contains a variety of food groups, and the DDS has been shown to be a good predictor for micronutrient adequacy and nutrition outcomes (Steyn et al 2006). Specifically for Ethiopia, the household DDS is strongly and positively associated with household's mean probability of nutrient adequacy (Mekonnen et al 2020). We deviated from the standard practice of using a 24-hour recall and used a one-week recall instead.…”
Section: Questionnaire and Key Variablesmentioning
confidence: 99%
“…14 Assigning a value of one for each food group that the household consumed from and summing, we can construct the HDDS in which higher scores indicate a better household food security situation. HDDS is a widely used food security indicator and previous work has found it to be highly correlated with caloric availability (Hoddinott and Yohannes 2002) and nutrient adequacy (Mekonnen et al 2020). In May, June, and July rounds, we administered the standard HDDS module that asks households whether they consumed from a given food group.…”
Section: Resultsmentioning
confidence: 99%
“…Of note is that even the lowest mean HDDS recorded during the pandemic is well above average scores recorded in other surveys administered before the pandemic. Using the nationally representative 2015/2016 Living Standards Measurement Study‐Integrated Surveys on Agriculture (LSMS‐ISA) survey for Ethiopia, Mekonnen et al (2020) estimate an average HDDS of 6.2 for rural areas and 7.9 for urban areas. Moreover, in July 2018, the mean household diet diversity score in chronically food insecure areas supported by the rural PSNP was less than five food groups (Berhane et al 2019a, Berhane et al 2019b).…”
Section: Resultsmentioning
confidence: 99%
“…This puts them at increased risk for any micronutrient de ciency in a household. Other studies in Ethiopia have also reported dietary diversity was a strong predictor of micronutrient adequacies with direct relationship with food security, household income and health access of a community [53,54] Ethiopia is one the highest NTD burdened country, with a prevalence rate ranging from 0.23%-40.3% [55,56]. For pregnant women, reports indicate 12% folate de ciency in Ethiopia, 3% in Kenya, and 4% in Nigeria [5].…”
Section: Discussionmentioning
confidence: 99%